In silico and in vitro Structural Analysis on the Interaction of Calmodulin and Calmodulin-Binding Motif of FKBP35 from Plasmodium knowlesi - Sazlinawatie, Aladin; Cahyo, Budiman; Arifin, Muhammad; Rafida, Razali (Science Publications, 2025)
FK506-binding protein 35 (FKBP35) is a peptidyl-prolyl cis-trans isomerase found in Plasmodium knowlesi, a zoonotic malaria parasite responsible for concerning cases of malaria infection in East Malaysia. This protein contains a segment known as the calmodulin-binding motif (Pk-CBM), which is predicted to facilitate interaction with calmodulin from P. knowlesi (Pk-CaM). Although this interaction is considered promising for future antimalarial drug development, it has not yet been experimentally demonstrated. This study aims to investigate the binding between the Pk-CBM of FKBP35 and Pk-CaM through both in silico and in vitro approaches, with a focus on the structural features of this interaction. To address this, three-dimensional models of Pk-CaM and Pk-CBM were first constructed using SWISS-MODEL, and the docking complex was generated using HADDOCK. Subsequently, MD simulations were carried out using the YASARA structure package to assess the stability of the interaction over a period of 100 ns, utilizing the AMBER14 force field under conditions of 298 K (25°C) and pH 7.4 in an explicit water environment. Furthermore, to confirm the in silico binding event, an in vitro experiment was conducted to assess the binding between Pk-FKBP35 and the CBM using circular dichroism and anilinonaphthalene-1-sulfonic acid (ANS) fluorescence assays. The docking simulation revealed that the C-terminal segment of Pk-CBM, particularly the IL motif, is essential for binding to Pk-CaM, with detailed mapping of residue-specific interactions provided by LigPlot. These computational results were corroborated by in vitro studies, which demonstrated that the binding event significantly altered the secondary structure of Pk-CaM and involved its hydrophobic regions. Together, these findings confirm a significant interaction between Pk-CaM and Pk-CBM, suggesting potential novel druggable targets for antimalarial drug design aimed at P. knowlesi.